The clinical utility of circulating human papillomavirus across squamous cell carcinomas - Karen-Lise G. Spindler; Anne V. Jakobsen; Jesper G. Eriksen; Lars Fokdal; Marianne Nordsmark; Lise B. J. Thorsen; Karen L. Wind; Anna C. Lefevre; Jens Overgaard (Acta Oncologica)
Background and purpose: The similarities in biology, treatment regimens and outcome between the different human papillomavirus (HPV) associated squamous cell carcinomas (SCCs) allow for extrapolation of results generated from one SC tumor type to another.